2009
DOI: 10.1111/j.1468-2478.2009.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

A Sectoral Analysis of Human Rights and FDI: Does Industry Type Matter?

Abstract: While there is a considerable degree of consensus about the economic determinants of foreign direct investment (FDI), the role of socio-political factors has only recently come under scrutiny. In this study, we build upon research on one such factor, human rights. Specifically, whereas extant research into FDI examines aggregate investment indices, we seek to disaggregate the analysis of FDI to further assess the role of human rights, namely physical integrity rights, in investment decisions. As FDI is a heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 58 publications
1
69
0
Order By: Relevance
“…17 We attempted to subdivide manufacturing sector FDI data into high and low skill subsectors, based on the classification system devised by Blanton and Blanton (2009). The service sector is heterogeneous in terms of skill bias, and we anticipated that some service subsectors would perhaps be more strongly associated with inequality than others.…”
Section: Service Subsector Fdi and Inequalitymentioning
confidence: 99%
“…17 We attempted to subdivide manufacturing sector FDI data into high and low skill subsectors, based on the classification system devised by Blanton and Blanton (2009). The service sector is heterogeneous in terms of skill bias, and we anticipated that some service subsectors would perhaps be more strongly associated with inequality than others.…”
Section: Service Subsector Fdi and Inequalitymentioning
confidence: 99%
“…Empirically, most studies assessing rights and FDI analyze cross‐sectional time‐series data with a particular kind of commonly used autoregressive distributed lag model (ADL). For instance, Kim and Trumbore () use a dead start model and Blanton and Blanton (, , ) use a partial adjustment model, a static model, and a dead start model . However, commonly employed ADLs impose particular restrictions that may not be justifiable.…”
Section: Methodsmentioning
confidence: 99%
“…Recognizing that the causal arrow may go in the other direction, Blanton and Blanton (, , ) examine how respect for human rights affects investors' decisions. They find that human rights abuses, as measured by the Political Terror Scale, are negatively and statistically significantly related to FDI inflows (2006).…”
Section: Reversing the Causal Arrow: When Rights Affect Fdimentioning
confidence: 99%
“…As discussed in section III, several scholars have shown that policymakers often hope WTO membership will not only expand trade, but help them attract more foreign investment. Scholars have also examined the effects of FDI on government respect for human rights (Richards, Gelleny, and Sacko 2001; Blanton and Blanton 2009). Thus, FDI may have an important effect in both stages of our analysis.…”
Section: Alternate Specificationsmentioning
confidence: 99%